An Overview of Experiential Learning in Nursing Education - Murray, Rhoda (Advances in Social Sciences Research Journal, 2018)
Experiential learning is an important methodology within the theoretical belief of adult education. Experiential learning is an educational orientation aimed at integrating theoretical and practical elements of learning that emphasizes the importance of experience for learning. In nursing education, learning through experience is called “hands-on” learning, or learning by doing (Burnard, 1993). Experiential learning centers on active pedagogical strategies that engage students in the learning process. Strategies include simulations, role-playing, clinical experiences, case studies, problem or inquiry based learning, and concept mapping. Additionally, experiential learning can occur in the field or classroom. This paper will provide an overview of experiential learning based on the works of Dewey (1938) and Kolb (1984), explain how experiential learning differs from other types of learning used in nursing classrooms, and describe the challenges of experiential learning theory as it relates to nursing education. Key words: Experiential learning, Dewey, Kolb, nursing education, pedagogy